Export/import procedures and documentation - Bade, Donna L. (AMACOM, American Management Association, 2015)
This comprehensive answer book supplies readers with a clear view of the entire export/import process, explaining the ins and outs of shipping and insurance; customs and export control requirements; distributors vs. agents; payment mechanisms; and transportation issues. The fifth edition of Export/Import Procedures and Documentation contains new and expanded information on topics including corporate oversight and compliance; valuation; licensing requirements and exceptions; International Commerce Trade Terminology; The Export Control Reform Act; the shifting definition of "Country of Origin;"